The Correlation Between Age, Comorbidities, and Vaccination With The Mortality Rate of Covid-19 Patients - Muin, Abdul; Menap, Menap (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
The objective of this study is to determine the primary factors that contribute to the mortality rate of COVID-19 in Indonesia, with a specific focus on age, comorbidities, and vaccination status. A retrospective analysis was performed utilizing patient data obtained from the West Lombok Health Office in the year 2020. The findings indicated that individuals aged 59 years or older had a considerably higher risk of mortality, with an odds ratio of 0.065 (95% confidence interval: 0.014 - 0.305). Comorbidities, specifically hypertension and diabetes mellitus, were found to be substantial risk factors. The odds ratio for hypertension was 63.64 (95% CI: 1.232 - 30.608), while the odds ratio for diabetes mellitus was 2.00 (95% CI: 1.593 - 2.512). The study revealed that being vaccinated considerably decreased the likelihood of death, with an odds ratio of 0.071 (95% CI: 0.015 - 0.334). Nevertheless, engaging in self-isolation was found to greatly elevate the likelihood of mortality, as indicated by an odds ratio of 195.429 (95% confidence interval: 22.894 - 1668.196). The Chi-Square test revealed a statistically significant association between vaccination status and COVID-19 mortality, with a p-value of 0.000 < 0.05. The logistic regression analysis revealed that the type of isolation had a very significant and large effect on COVID-19 mortality. The odds ratio (Exp(B)) was 96.604, showing a strong association between the type of isolation and the mortality rate. The p-value was 0.000, further confirming the statistical significance of this relationship. Therefore, the type of isolation plays a critical role in determining the death rate of COVID-19 patients. These findings emphasize the significance of immunization programs and efficient isolation measures in decreasing COVID-19 mortality. In summary, this study offers significant information that can be used to develop more focused health policies in Indonesia. It emphasizes the crucial importance of vaccination and isolation measures in effectively managing the COVID-19 pandemic. Gaining insight into these factors can assist in customizing health treatments to mitigate risks and enhance clinical outcomes for COVID-19 patients in Indonesia